Intramuscular iron supplementation enhances intestinal barrier function in weaned piglets challenged with enterotoxigenic Escherichia coli - Tian, Chenying; Zhang, Xiaofeng; Xu, Yecheng; Miao, Linfeng; Zhao, Jing; Xiong, Qingqing; Zhang, Yuhui; Jiang, Shouchuan; Han, Yu; Du, Huahua (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSince iron is an essential mineral for both host and microbial communities, how to scientifically replenish the iron in the context of bacterial infection has become a critical issue. The aim of this study was to compare the influence of intramuscular and oral iron supplementation on the progression of bacterial infection. MethodsWeaned piglets served as an experimental model for iron supplementation following enterotoxigenic Escherichia coli (ETEC) K88 infection. Piglets in control and oral iron supplementation groups received FeSO4 orally, while those in the intramuscular iron supplementation group were administered iron dextran (FeDex) via intramuscular injection. After challenge, piglets were euthanized, and serum and small intestinal tissues were collected for biochemical analysis, histological examination, inflammatory response assessment, gut microbiota profiling, and iron metabolism evaluation.ResultsIntramuscular iron supplementation alleviated the clinical symptoms of bacterial infection, decreasing the diarrhea rate by 53% and mitigating the inflammatory response with lower serum levels of pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-8. Compared to oral iron supplementation, intramuscular iron supplementation significantly mitigated the intestinal damage caused by ETEC K88 infection by increasing the ratio of villus length to crypt depth, and repairing epithelial tight junction. Furthermore, intramuscular iron supplementation also protected the function of intestinal goblet cells and improved iron metabolism of infected piglets.ConclusionIntramuscular iron supplementation is more effective during infection than oral iron supplementation.